Prevalence and Correlates of overweight and obesity among school children in Guwahati city, Assam - Baruah, Chetanjit (Indian Journal of Community Health, 2018)
Background: Childhood obesity is one of the most serious public health challenges of the 21st century. Obese children are at increased risk for heart disease, diabetes, stroke, cancer and osteoarthritis. Aim & Objective: To study the prevalence of overweight and obesity & its correlates among school children of Guwahati city. Materials and Method: School based cross sectional study was done among the students of 8th to 10th standard of Guwahati city, Assam. 465 school children were selected by multistage simple random sampling. Data was collected using a pre-designed, semi-structured questionnaire. Results: Prevalence of overweight and obesity was found to be 5.4 % & 2.8 %.and it was significantly more among those who were Non-vegetarian, whose breakfast habit were irregular, don’t consume fruits, consume fast food daily, junk food daily, carbonated drinks daily, don’t play outdoor games and use vehicles as mode of transport to school. Conclusion: Prevalence of overweight and obesity was found to be more among students having modifiable risk factors.